Palladium(II)-Catalyzed C–H Acylation with Arylglycine Derivatives - Fan, Weizheng; Su, Jiapeng; Feng, Bainian (Synlett, 2015)
A novel palladium(II)-catalyzed ortho acylation of arenes with arylglycines in the presence of Cu(OAc)2 and K2S2O8 to afford the benzophenones was developed. This direct C–H acylation is suitable for a broad range of substrates. The control experiments suggested a possible oxidative addition mechanism.
Keywords: palladium(II)-catalyzed; ortho acylation; arylglycine; C–H activation; oxidative addition